STUDI KASUS: IBU HAMIL DENGAN NYERI PUNGGUNG: Case Study : Pregnant Women With Back Pain - Agustin Dwi Syalfina; Sari Priyanti; Dian Irawati (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2022)
Back pain is a common symptom experienced during pregnancy. Even though the prevalence is high, this back pain complaint is not considered a serious problem in pregnancy even though it will have a bad impact on the quality of life of pregnant women if not properly managed. This study aims to determine the signs and symptoms and management of third trimester pregnant women with back pain. The type of research conducted is descriptive epidemiology case study type. The research subject Mrs. "Y" aged 35 years at 38 weeks of gestation. Collecting data with home visits to identify subjective and objective data and provide management to research subjects. The data obtained were documented in a midwifery care format. Mrs "Y" complained of back pain because her pregnancy was included in the third trimester, the stomach was already enlarged so that the body shape was hyperlordosis, and the burden of domestic roles that Mrs "Y" had to do increased the degree of back pain she felt. But Mrs “Y” did not feel any anxiety about this discomfort. The midwifery care provided is doing the left side sleeping position, pregnancy exercise, pregnancy massage and deep breathing relaxation. This treatment was able to reduce Mrs "Y"'s back pain based on the evaluation of the third visit by the researcher. Health workers are expected to always pay attention to the complaints of pregnant women even though they are physiological to maintain the quality of life of pregnant women to be good.